Hazardous waste compliance - Florczak, Clifford M., 1951-; Roughton, James E. (Boston : Butterworth-Heinemann, 2001)
Hazardous Waste Compliance concentrates on government regulations as they relate to hazardous waste and other hazardous materials. The main focus of this book is on how to comply with these requirements as well as on other best management practices (BMP), which will ensure worker safety and business protection from the risk of the commercial penalties associated with regulations breaches. The authors provide the reader with useful techniques to enhance worker protection and promote efficiency, productivity and cost effectiveness, along with achieving the necessary quality standards for the wor.
Introduction -- Compliance issues -- Planning activities -- Conducting a job hazard analysis -- Developing a site-specific health and safety plan -- Development of a site-specific health and safety plan -- Implementing the safety plan -- Training requirements -- Personal protective equipment -- Decontamination activities -- Emergency preparedness and response.
Includes bibliographical references and index.
Keywords: Hazardous substances -- United States; Hazardous substances -- Safety measures -- Government policy -- United States; Hazardous waste site remediation -- United States -- Safety measures; Electronic books